(untitled) (Biocenosis, 2023)
To conclude the year 2023, issue number 34 (2) of the Biocenosis magazine presents its readers with a selection of articles that address various topics of current interest. These contribute valuable information for the management and preservation of the environment, a continuous challenge for Costa Rica, a country recognized worldwide for its commitment to environmental conservation.